Effects of Ionizing Radiation on the Electrical and Optical Properties of Polyvinyl Alcohol/Aniline Hydrochloride Blend Films - Othman, Azian (2007)
attempt was made to produce polyvinyl alcohol (PVA)/polyaniline (PANI) conducting polymer composites from PVA/Aniline hydrochloride (AniHCl) blends via radiation induction. Films of PVA/AniHCl blends at various AniHCl compositions were initially prepared by solvent casting method. The films were then irradiated with Co60 gamma rays to doses up to 20 kGy. The optical properties were measured by using a UVVisible spectrophotometer in the wavelength range of 200800 nm. The formation of PANI was observed when the films changed colour from colourless to light green at 20 kGy. However the amount of PANI formed was limited as the green colour did not reveal significantly in the absorption spectra, but instead the main absorption band was peaking at 315 nm corresponding to the formation hydrochloric acid by radiation. The absorbance data at 315 nm were fitted to an exponential law and found to have a relationship between dose sentivity 0 " D and AniHCl composition C as 0 " D = 0.3133C + 3.18. The radiation caused bond scission of covalent bonds of AniHCl and hydrolysis of water to produce Cl , OH , and H + ions in the blends and as well as PANI that lead to the changes in optical properties and conductivity of irradiated PVA/AniHCl blends. The absorption spectra of irradiated PVA/AniHCl films were analyzed further for absorption edge, activation energy, and band gap energy. From the plot of absorption coefficient a versus photon energy hv, the absorption edge for 9% AniHCl decreases from 4.76 to 4.66 eV when the dose increases from 0 kGy to 20 kGy and that for 29%AniHCl the value decreases from 4.52 to 4.40 eV. From the slope of ln a versus hv, we found the optical activation energy D E decreases from 1.08 to 0.87 eV for 9% AniHCl and from 0.33 eV to 0.25 eV for 23% AniHCl. The optical band gap for the direct allowed transition was determined from the intercepts of the extrapolated linear part of the plot of (ahν) 2 against hν,. The band gap energy decreases from 2.60 to 2.38 eV for 9% AniHCl and that for 29% AniHCl the value decreases from 2.46 to 2.14 eV . The conductivity of irradiated PVA/AniHCl films was measured at room temperature and in the frequency range from 20 Hz to 1 MHz by means of an impedance analyzer. The conductivity at 20 Hz for 9% AniHCl increases from 9.41 x 10 7 Sm 1 at 0 kGy to 5.01x10 6 Sm 1 at 20 kGy. The conductivity for 23% AniHCl increases from 1.85×10 5 Sm 1 at 0 kGy to 5.78×10 5 Sm 1 at 20 kGy. The frequency exponent values of s1 and s2 were determined from the gradients of the linear plots of log s(w) versus log w. The value of s decreases with the increase of dose and AniHCl composition. The s1 value varies from 0.04 to 0.20 and that of s2 its value varies from 0.30 to 0.90. The dc conductivity extracted from the ColeCole plots of the complex impedance Z” vs. Z’, shows the dc conductivity increases with dose by an exponential law. The slope of the linear regressions from ln s (w ) dc versus D plot was used to determine the value of dose sensitivity 0 ' D , for conductivity. The 0 ' D and 0 s values obtained are AniHCl dependent given by 0 ' D =0.3226C +10.904 and 0 s =1.0 x 10 6 C – 4.0 x 10 6 where C is AniHCl composition.